A educação superior no contexto da sociedade contemporânea: os sentidos e intencionalidades da internacionalização no PNPG (2011-2020) - Trevisol, Marcio Giusti (2020)
The research developed aimed to understand the meanings and intentionalities of the National Postgraduate Plan (NPP) (2011-2020) in relation to the internationalization of Higher Education. The investigative problem is to point out: what are the interests and intentionalities present in the National Postgraduate Plan (2011-2014) regarding the aspects of internationalization? The research is based on the objective of pointing out the meanings and intentionalities of internationalization in the National Post-graduation Plan (2011-2020), based on the categories of analysis, namely, internationalization as cooperative and supportive cooperation, mercantilized internationalization, internationalization for the formation of universal citizenship, and neoliberal internationalization and globalization. It is a documentary research and characterized as analytical, with historical method and dialectic methodology. The universe of the research is the National Postgraduate Plan (2011-2020). From the data collected and the analysis, it is possible to ascertain that the document presents intentionalities and interests linked to the aspects of the economy of flexible accumulation and has a broad agreement with the neoliberal and mercantile assumptions. The presence of these interests and organizational principles in the NPP (2010) hinders a perception of internationalization linked to the aspects of solidarity and cooperation that could contribute to the formation of a universal citizenship. In addition to these elements, it is important to point out that the NPP (2010), by placing greater emphasis on strategic areas for the development of the country, endangers the humanities and establishes as a standard a concept of utilitarian higher education based on the objectivity of quantifiable and financially viable results for the productive mode of flexible accumulation. This condition puts at risk the internationalization of higher education as a perspective of solidarity, cooperation, democracy, and public good.